THEORITICAL FEASIBILITYOF GUIDED DISCOVERY WORKSHEET IN KINGDOM ANIMALIA SUB MATTER FOR SENIOR HIGH SCHOOL CLASS X - FIRMAN ZARKASY (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Learning process especially for Science class should be designed to be interactive and inspiring so that the students will be motivated to participate actively. In material about animals kingdom for X class, there is one of basic competences stated that the students are able to describe phylum in animal kingdom and its role in daily life. Thus, this study focuses on Echinodermata phylum. Based on preliminary study, 51.7% of the students of SMAN 1 Lamongan had difficulties in learning one of materials about phylum of animal kingdom, the medium that was used by the teacher was not good enough. Therefore, the students’ working sheets entitled “Guided Discovery” was needed to develop as well as the model of Echinodermata to support Biology learning process for X class. The aim of this study was to create students’ working sheets entitled “Guided Discovery” and describe its suitability theoretically. This reseach was developmental study, which was from the students’ working sheets entitled “Guided Discovery”. The development of medium was based on 4-D method (disseminate steps). It took time from November 2012 until February 2013. Method of data collection using validation sheet. The result of this study showed that the students working sheets entitled “Guided Discovery” was not only worth using theoretically with 94% which includes the identity of 91%, display 97%, English 94%, content 94%, and 94% characteristic of guided discovery. In summary, the students’ working sheets entitled “Guided Discovery” can be used for learning purposes. Keyword: students worksheets “Guided Discovery”, Echinodermata, Biology for X class.